Discovering Large-scale Structure at 2 < z < 5 in the C3VO Survey - Denise Hung; Brian C. Lemaux; Olga Cucciati; Ben Forrest; Ekta A. Shah; Roy R. Gal; Finn Giddings; Derek Sikorski; Emmet Golden-Marx; Lori M. Lubin; Nimish Hathi; Giovanni Zamorani; et al. (The Astrophysical Journal)
The Charting Cluster Construction with VUDS and ORELSE (C3VO) survey is an ongoing imaging and spectroscopic campaign aiming to map out the growth of structure up to z ∼ 5 and was born from the combination of the Visible Multi-Object Spectrograph Ultra Deep Survey and the Observations of Redshift Evolution in Large-Scale Environments (ORELSE) survey. As we previously accomplished with the ORELSE survey, we apply our technique known as Voronoi tessellation Monte Carlo (VMC) mapping to search for serendipitous galaxy overdensities at 2 < z < 5 in the three C3VO fields. We also apply the same technique to mock observations of simulated galaxies with properties derived from the GAlaxy Evolution and Assembly semianalytic model in order to judge the effectiveness of our search algorithm as a function of redshift, total mass, and fraction of spectroscopic redshifts. We find completeness and purity values of the order of 30%–50% for $log(M_{z=0}/M_{\odot })\gt 14$ and 2 < z < 4, with a strong dependence on mass and redshift, with values as high as ∼80% and ∼70%, respectively, in the best-case scenario for $log(M_{z=0}/M_{\odot })\gt 14.5$ . In the C3VO fields, we were able to recover many of the previously known structures in the literature as well as find hundreds of new overdensity candidates, once again demonstrating the powerful capabilities of VMC mapping when applied to wide-field optical and infrared galaxy evolution surveys at ever higher redshifts.